Embracing the Knowledge Society for a Sustainable Future of a Halal Industry - Hashim, Yumi Zuhanis Has-Yun; Handayani, Dini Oktarina Dwi; Mohd Nazori, Mohd Nazir bin; Mustari, Sohela; Shiha, Habiba Khatun; Mohd Salleh, Hamzah (Halal Studies and Society, 2025)
This study aimed to examine the evolving concept of the Knowledge Society (KS) and its implications for a halal industry through conventional and Islamic lenses. UNESCO and contemporary scholars defined KS as a system that generated and applied knowledge for human progress. This study reinterpreted the concept within an Islamic epistemological framework, particularly the tawhidic paradigm that viewed knowledge as a path toward divine pleasure and holistic well-being. Using a narrative review method, the study analyzed existing literature to bridge the gap between Western secular notions of KS and the Islamic worldview that integrated ethical, spiritual, and societal dimensions. The results showed that embedding tawhidic values in knowledge creation enhanced the authenticity and sustainability of a halal industry. Current developments were also identified, such as a halal Knowledge Centre, and challenges, including regulatory complexity, limited study integration, and uneven certification systems. In conclusion, establishing a halal KS rooted in Islamic ethics and collaborative learning offered a novel framework for achieving sustainability, integrity, and inclusive growth across the global halal ecosystem.